Consecinţe şi riscuri asupra calităţii vieţii asociate schimbărilor climatice - Humă, Cristina (Calitatea Vieții, 2017)
The paper highlights some of the main consequences and risks that climate change has on society and how it affects the quality of life of the population. We have in mind the impact of climate change, which is related to extreme weather events such as heat waves and cold waves, floods, droughts, etc., which have important environmental and social effects. We have mainly referred to changes in air quality, quantity and quality of water, ecosystems, agriculture, livelihoods, infrastructure that can affect human health, increasing the risk of harm, illness and even death among people, and can also cause considerable material loss. These issues have been addressed both globally and nationally. The study is based on an analysis of statistical data that reflects the direct impact – human loss, affected persons and material damage – related to extreme climatic conditions and some indirect impact assessments that significantly influence the quality of life of the population. In the analysis, estimates and statistical data were used at international, European and national levels.